MANAGEMENT OF CONGENITAL BILATERAL ABDUCTOR VOCAL CORD PALSY FOR TRACHEOSTOMY IN A NEONATE - Abraham, Valsa; Osahan, Narjeet Kaur; Ria (International Journal of Research -GRANTHAALAYAH, 2023)
Bilateral abductor vocal cord palsy is very rare, and is still the second most common cause of congenital stridor in neonates. It can also cause breathing difficulty and cyanosis in neonates during increased crying spells, and hence eventually might require invasive airway management. This is a case report of a 7-day old neonate posted for tracheostomy under general anaesthesia.